Multitemporal land use change analysis in San Fernando, Tamaulipas for the Period 1987 to 2017 - Salinas-Castillo, Wilver Enrique (Universidad Autónoma de Tamaulipas, 2020)
Land Use Change (LUC) tends to have a negative effect on global atmospheric and climate processes. The objective of this paper was to assess the LUC for the San Fernando, Tamaulipas, Mexico municipality, during the period comprehended between 1987 and 2017. The classification by segmentation method was applied to satellite images obtained from 1987, 1997, 2007 and 2017, which allowed for a reduction in the noise that is characteristic of pixel-based classification. However, it was necessary to edit the results in order to recover human settlements, eliminate clouds and shadows, and reduce the confusion between vegetation cover and cultivated agricultural land in order to avoid introducing artificial LUC in the statistics produced. The multitemporal analysis showed a clear trend in the reduction of vegetation cover (- 6.53 %) and of areas devoid of vegetation (- 1.71 %). Likewise, the results also highlight a significant increase of agricultural land (+ 7.61 %), which seems to be unassociated with the increase of human settlements (+ 0.08 %). The developed methodology seems to be appropriate and of easy implementation to carry out the LUC analysis in other regions of interest.